2020
DOI: 10.47203/ijch.2020.v32i01.017
|View full text |Cite
|
Sign up to set email alerts
|

Spectacle wear and factors associated with non-compliance among children of 5-15 years

Abstract: Introduction: Refractive errors are the commonest cause of visual impairment in school children worldwide. They are correctible and after screening, spectacles can easily enhance vision. This can be achieved only when spectacles are used regularly.  Objective: This study was conducted to study the compliance of spectacles wear among children and to determine the reasons associated with non-compliance. Methodology: 400 children in the age group of 5-15 years with refractive errors attending the eye OPD, using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Similar findings were observed in Aligarh, Uttar Pradesh. 5 On contrary, a study done in Rohtak, Haryana, observed that older children were more non-compliant to spectacle wear than younger children. 7 Children with anisometropia were more likely to be noncompliant to spectacle wear as compared to children without anisometropia.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Similar findings were observed in Aligarh, Uttar Pradesh. 5 On contrary, a study done in Rohtak, Haryana, observed that older children were more non-compliant to spectacle wear than younger children. 7 Children with anisometropia were more likely to be noncompliant to spectacle wear as compared to children without anisometropia.…”
Section: Discussionmentioning
confidence: 95%
“…Statistically significant association was observed between spectacle wear non-compliance and other variables such as astigmatism, Intolerance to glasses, Glasses Lost, Glasses Broken, Concerned teasing and Cost issues. Mehnaz et al 5 observed statistically significant association between spectacle wear non-compliance and concerned teasing.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations